A ‘Monster’ in Holy Grounds: Saint Christopher the Cynocephalus in the Taxiarches Church at Melies of Pelion in Greece - Gkounis, Spyridon (Troianalexandrina, 2011)
Abstract In the Taxiarches church at Melies of Pelion, there is, among other interesting and rare wall paintings, a depiction of Saint Christopher dating from 1774. What is unusual about this painting is that the saint is depicted with the head of a dog. The common theme for representations of Saint Christopher is, as his name suggests, a tall man carrying Christ across a stream. The eastern tradition of the saint’s Vita, refers to his origin from the race of the Cynocephali. This tradition was transferred to the west earlier than the 10th century and was transmitted by Irish monks to the British Isles. Only a couple of such depictions, however, survive there and few in the regions of the Orthodox Church, all from the 17th century onwards. By looking back on the ancient lore of the race of the Cynocephali, this article tries to identify the connection between the two iconographic traditions of Saint Christopher. The fresco is also linked to the iconographic program of the whole church as many of the themes are rare and indicate a relation, or at least a knowledge, to the west.